Sistema para gerenciamento de atendimentos de setor médico-odontológico - Formentini, Marcelo Jose (2015)
The records of attendance in the medical and dental sectors of the Federal Technological University of Paraná, Campus Pato Branco, are being carried out so far on manual spreadsheets, which complicates the monitoring of information as well as reporting. Because of this, an application was developed to facilitate and assist in recording the calls of these sectors and referrals made by the medical sector. A simple inventory control for those medicinal products has also been implemented. The care management system of medical and dental sectors is a web application characterized as rich interface was developed using Java Enterprise Edition technology, JavaServer Pages, JavaServer Faces, among others.